conveyor
By using a base layer and a surface layer with specific components and structures on the conveyor belt of the image forming device, the vibration and sliding sound problems caused by changes in surface shape and sliding properties during long-term use are solved, and high sliding properties and wear resistance are achieved.
Patent Information
- Application Number
- CN202180062473.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-09-29
- Filing Date
- 2021-09-27
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2041-09-27
AI Technical Summary
In the image forming device of electrophotography and inkjet, the conveyor belt used for a long time has caused vibration and sliding sounds between the cleaning blade and the conveyor belt due to changes in surface shape and sliding properties.
A conveyor belt with a cylindrical base layer and an outer peripheral surface layer is used. The base layer is composed of polyimide and polyamideimide, and has an elastic modulus of 3GPa or more and 7GPa or less. The surface layer is composed of a cured body of a resin composition of a fluororesin, an isocyanate curing agent and a silicone copolymer. The silicone copolymer contains 95 mol% or more and less than 100 mol% of a silicone unit, and the addition amount is 1 part by mass or more and 5 parts by mass or less.
By improving the elastic modulus of the base layer and the sliding property of the surface layer, vibration and sliding sound between the cleaning blade and the conveyor belt are suppressed, ensuring high sliding properties and wear resistance of the conveyor belt in long-term use.
Smart Images

Figure CN116096577B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a conveyor belt which is provided in an image forming apparatus of an electrophotographic method or an inkjet method and is used for conveying a recording medium such as paper. Background Art
[0002] In electronic photography and inkjet image forming devices such as copiers, printers, and fax machines, a conveyor belt configured as an endless belt is used to form an image while setting and conveying a recording medium such as paper. In image forming devices, the conveyor belt used to convey the recording medium is mostly formed into a two-layer structure of a base layer and a surface layer formed on the outer peripheral surface of the base layer. Patent documents 1 to 3 disclose setting the composition and characteristics of the base layer and the surface layer of the conveyor belt from the viewpoint of achieving the desired characteristics of the conveyor belt such as adsorption and cleanliness to the recording medium.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2001-310836
[0006] Patent Document 2: Japanese Patent Application Publication No. 2008-94605
[0007] Patent Document 3: Japanese Patent Application Publication No. 2011-73804 Summary of the invention
[0008] Problems to be solved by the invention
[0009] In an image forming apparatus using an electrophotographic method or an inkjet method, toner, ink, and paper dust may adhere to the conveyor belt. Therefore, in order to remove these adhered materials, the surface of the conveyor belt is scraped off with a cleaning scraper. If the image forming apparatus is used continuously for a long time, when the cleaning scraper is slid in contact with the conveyor belt, vibration and sliding noise may occur between the cleaning scraper and the conveyor belt. In particular, when the surface shape and sliding properties of the conveyor belt change due to long-term use, sliding noise is likely to occur.
[0010] The problem to be solved by the present invention is to provide a conveyor belt for an image forming apparatus which is less likely to generate sliding noise caused by abutment and sliding of a cleaning blade even when used for a long period of time.
[0011] Technical solutions to the problem
[0012] In order to solve the above-mentioned problems, the conveyor belt involved in the present invention is a conveyor belt for an image forming apparatus, which has a cylindrical base layer and a surface layer formed on the outer peripheral surface of the base layer, the base layer contains at least one of polyimide and polyamide-imide, the base layer has an elastic modulus of 3 GPa or more and 7 GPa or less, and the surface layer is constituted as a cured product of a resin composition containing a fluororesin having a hydroxyl group, an isocyanate curing agent and a silicone copolymer, the silicone copolymer is a copolymer containing a silicone unit having a siloxane skeleton and other units not having a siloxane skeleton, the silicone copolymer has a hydroxyl group, the content ratio of the siloxane unit in the silicone copolymer is 95 mol% or more and less than 100 mol%, and the addition amount of the silicone copolymer in the resin composition is 1 mass part or more and 5 mass parts or less relative to 100 mass parts of the total of the fluororesin and the isocyanate curing agent.
[0013] In addition, another conveyor belt involved in the present invention is a conveyor belt for an image forming apparatus, comprising a cylindrical base layer and a surface layer formed on the outer peripheral surface of the base layer, the base layer containing at least one of polyimide and polyamide-imide, the base layer having an elastic modulus of 3 GPa or more and 7 GPa or less, the surface layer being constituted as a cured product of a resin composition containing a fluororesin having a hydroxyl group, an isocyanate curing agent, and a silicone copolymer, the silicone copolymer being a copolymer containing a silicone unit having a siloxane skeleton and other units not having a siloxane skeleton, the silicone copolymer having a hydroxyl group, the content ratio of the siloxane unit in the silicone copolymer being 40 mol% or more and 70 mol% or less, and the amount of the silicone copolymer added in the resin composition being 1 part by mass or more and 5 parts by mass or less relative to 100 parts by mass of the total of the fluororesin and the isocyanate curing agent.
[0014] The surface layer may contain a fluorine-based or silicone-based leveling agent.
[0015] The micro hardness of the surface layer can be 30N / mm 2 Above and 200N / mm 2 the following.
[0016] The base layer may have a thickness of 50 μm or more and 90 μm or less.
[0017] The silicone copolymer may be composed of any one of methyl methacrylate, 2-hydroxyethyl methacrylate, and trimethylolpropane as the other unit, and acrylate-modified silicone oil and OH-modified silicone oil as the silicone unit.
[0018] Effects of the Invention
[0019] In the conveyor belt involved in the above invention, by making the base layer have an elastic modulus within the above-mentioned predetermined range, vibration caused by surface deformation accompanied by bending is not easy to occur between the cleaning scraper and the conveyor belt. In addition, by making the surface layer composed of a solidified body of a composition containing both fluororesin and silicone copolymer, and making the content ratio of siloxane units in the silicone copolymer and the addition amount of silicone copolymer within the above-mentioned predetermined range, sufficient sliding properties are ensured on the surface of the conveyor belt. In addition, the surface layer has high wear resistance, and its sliding properties can be maintained at a high state even if it is abutted and slid by the cleaning scraper for a long time. Under the action of both the above-mentioned base layer and the surface layer, even if the conveyor belt is used for a long time and the cleaning scraper is abutted and slid, sliding sound is not easy to generate.
[0020] If the content ratio of the siloxane unit in the silicone copolymer is 95 mol% or more and less than 100 mol%, the siloxane concentration in the silicone copolymer is very high, so the friction coefficient of the surface layer becomes very low, and the force received from the cleaning blade becomes weak. As a result, the wear resistance and durable sliding properties of the surface layer are improved, and sliding noise is not easy to generate. In addition, if the content ratio of the siloxane unit in the silicone copolymer is 40 mol% or more and 70 mol% or less, the curability of the resin composition forming the surface layer is excellent, as a result, the wear resistance and durable sliding properties of the surface layer are improved, and sliding noise is not easy to generate.
[0021] Here, if the surface layer contains a fluorine-based or silicone-based leveling agent, the surface smoothness of the surface layer is improved, and as a result, the generation of sliding noise associated with contact and sliding with the cleaning blade can be particularly effectively suppressed.
[0022] Here, the micro hardness of the surface layer is 30N / mm 2 Above and 200N / mm 2 In the following cases, the conveyor belt has excellent sliding properties and bending resistance. As a result, the generation of sliding noise associated with the contact and sliding with the cleaning blade can be particularly effectively suppressed.
[0023] When the thickness of the base layer is 50 μm or more and 90 μm or less, vibration of the conveyor belt due to reduced rigidity and surface deformation associated with bending can be particularly effectively suppressed. As a result, the generation of sliding noise associated with contact and sliding with the cleaning blade can be particularly effectively suppressed.
[0024] When the silicone copolymer is composed of any one of methyl methacrylate, 2-hydroxyethyl methacrylate and trimethylolpropane as the above-mentioned other units, and acrylate-modified silicone oil and OH-modified silicone oil as silicone units, a silicone copolymer into which a hydroxyl group is introduced and in which the content ratio of the siloxane unit is adjusted to a predetermined range can be easily prepared. In addition, the silicone copolymer can contribute to effectively suppressing sliding noise in the conveyor belt. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a perspective view schematically showing a conveyor belt according to one embodiment of the present invention.
[0026] Figure 2 yes Figure 1 AA section view of the conveyor belt shown.
[0027] Figure 3 This is a schematic diagram illustrating the molecular structure of the cured product constituting the surface layer. DETAILED DESCRIPTION
[0028] Hereinafter, a conveyor belt according to an embodiment of the present invention will be described with reference to the accompanying drawings. In the following, various properties are properties evaluated at room temperature. In addition, a certain component being the main component of a certain material means that the component occupies more than 50% by mass of all the components of the material.
[0029] Figure 1 , Figure 2 The following is an overview of a conveyor belt 1 according to an embodiment of the present invention. The conveyor belt 1 is used to set and convey recording media such as paper in an image forming apparatus using an electrophotographic method or an inkjet method, such as a copier, a printer, or a fax machine. The conveyor belt 1 according to this embodiment is particularly suitable for use in an image forming apparatus using an inkjet method.
[0030] The conveyor belt 1 is configured as an endless belt and includes a base layer 2 and a surface layer 3 formed on the outer peripheral surface of the base layer 2. Even if the conveyor belt 1 is configured only of the base layer 2 and the surface layer 3, another layer such as an adhesive layer may be appropriately provided between the base layer 2 and the surface layer 3.
[0031] In an image forming apparatus, in order to scrape off attachments such as toner, ink, and paper scraps, a conveyor belt is abutted against and slid by a cleaning scraper (hereinafter, sometimes referred to as a scraper). Generally speaking, when the image forming apparatus is used continuously for a long period of time (hereinafter, sometimes referred to as a durable period), vibrations are easily generated between the conveyor belt and the scraper during the period when the conveyor belt is abutted against and slid by the scraper for a long period of time. When the scraper abuts against and slides on the conveyor belt accompanied by the generation of vibration, sliding sounds such as creaking sounds are sometimes generated. However, in the conveyor belt 1 involved in this embodiment, by making the base layer 2 and the surface layer 3 respectively have the structures described below, it becomes difficult to cause the generation of sliding sounds accompanied by the abutment and sliding of the scraper even in the durable period.
[0032] [Composition of the grassroots]
[0033] The base layer 2 is the base material of the conveyor belt 1. The base layer 2 is formed into a cylindrical shape and has a seamless structure without seams in the circumferential direction. The base layer 2 contains at least one of polyimide and polyamide-imide. Polyimide and polyamide-imide can be modified by functional groups. Polyimide and polyamide-imide are excellent in rigidity and durability, so they can be suitable as the constituent materials of the base layer 2 of the conveyor belt 1. It is particularly preferred to use polyimide to constitute the base layer 2. The base layer 2 can contain other components such as additives as long as it is a base layer with at least one of polyimide and polyamide-imide as the main component. As additives, conductive agents such as carbon black and graphite, fillers such as calcium carbonate, release agents, flame retardants, leveling agents, defoaming agents, etc. can be listed.
[0034] The base layer 2 has an elastic modulus of 3 GPa or more and 7 GPa or less. The elastic modulus of the base layer 2 can be evaluated by the tensile elastic modulus obtained by a tensile test. By making the base layer 2 have an elastic modulus of 3 GPa or more, the conveyor belt 1 has a sufficiently high rigidity, and the conveyor belt 1 is not easy to shake or vibrate. As a result, it becomes easy to obtain high sliding properties on the surface of the conveyor belt 1, which helps to suppress the sliding sound during durability. From the viewpoint of improving the above-mentioned effect, the elastic modulus of the base layer 2 is more preferably 4 GPa or more.
[0035] On the other hand, by suppressing the elastic modulus of the base layer 2 to 7 GPa or less, the surface of the base layer 2 is not easily deformed. If the elastic modulus of the base layer 2 is too high, when the conveyor belt 1 is supported by two shaft members and the conveyor belt 1 is rotated under tension, the bending deformation applied to the part in contact with the shaft member becomes difficult to eliminate even when it leaves the shaft member, and thus deformation is easily accumulated on the surface of the conveyor belt 1 after a long period of rotation. Such deformation of the conveyor belt 1 will lead to the formation of damage such as cracks and the generation of vibration. By suppressing the elastic modulus of the base layer 2 to 7 GPa or less, the bending resistance of the conveyor belt 1 is increased, and as a result, the generation of surface deformation and the vibration of the conveyor belt 1 associated therewith can be suppressed. From the viewpoint of improving the above-mentioned effect, the elastic modulus of the base layer 2 is more preferably 6 GPa or less.
[0036] Thus, by making the base layer 2 have an elastic modulus of 3 GPa or more and 7 GPa or less, high sliding property and bending resistance are ensured in the conveyor belt 1. As a result, even during the endurance, vibration is less likely to occur between the conveyor belt 1 and the scraper, and the generation of sliding sound associated with the sliding of the scraper is suppressed.
[0037] The thickness of the base layer 2 is not particularly limited, but is preferably 50 μm or more, more preferably 60 μm or more. In addition, it is preferably 90 μm or less, more preferably 80 μm or less. When the base layer 2 has a thickness within the above range, the sliding property and bending resistance of the conveyor belt are improved, thereby making the effect of suppressing the sliding sound during durability particularly excellent.
[0038] [Surface composition]
[0039] The surface layer 3 is formed as a cured product of a resin composition. The resin composition forming the surface layer 3 includes a fluororesin, an isocyanate curing agent, and a silicone copolymer. The fluororesin and the silicone copolymer each have a hydroxyl group. In the cured product, the hydroxyl groups of the fluororesin and the silicone copolymer form a urethane bond with the isocyanate group of the isocyanate curing agent. Specifically, as in Figure 3 As described in , the fluororesin A is crosslinked by the isocyanate curing agent B, thereby forming a main skeleton with a large amount of bonds, and the silicone copolymer C is bonded to the main skeleton and distributed in a region including the surface of the surface layer 3 .
[0040] Fluororesin becomes the main component of the resin composition constituting the surface layer 3, and plays a role as an adhesive polymer in the resin composition. The fluororesin is introduced with hydroxyl groups by modification, etc. Regarding the specific type of fluororesin, as long as it is a fluororesin that is appropriately dissolved in a solvent and forms a film in a liquid state and can be cured, there is no particular limitation, and examples thereof include fluorinated ethylene-vinyl ether copolymer (FEVE), polyvinylidene fluoride resin (PVDF), polychlorotrifluoroethylene resin (PCTFE), etc., and commercially available fluororesins as adhesive polymers can be preferably utilized. By constituting the surface layer 3 as a cured product of a resin composition containing fluororesin, the surface layer is made to show high adhesion to the base layer 2.
[0041] The isocyanate curing agent added to the resin composition is not particularly limited as long as it is a polyfunctional isocyanate compound. A curing agent composed of blocked polyisocyanate can be preferably used.
[0042] The silicone copolymer contained in the resin composition is a copolymer including a silicone unit having a siloxane skeleton and other units not having a siloxane skeleton. Preferably, in the silicone copolymer, the silicone unit and other units can be block copolymerized. The silicone copolymer has a hydroxyl group.
[0043] The type of silicone unit constituting the silicone copolymer is not particularly limited, and preferably dimethyl silicone resin, methylphenyl silicone resin, alkyl-modified silicone resin, alkyl-modified silicone resin, silicone oil consisting of OH-modified silicone oil, etc. The silicone unit may be one type or two or more types may be used in combination.
[0044] The other units constituting the silicone copolymer together with the silicone unit are not particularly limited as long as they are units that can copolymerize with the silicone unit, and units containing (meth) acrylic acid, (meth) acrylate, and trimethylolpropane as part or all of the structure can be preferably used as other units. In particular, if a molecule having a hydroxyl group is used as the other unit, the introduction of the hydroxyl group into the silicone copolymer can be easily performed and is preferred. For example, (meth) acrylate having a hydroxyl group can be preferably used as the other unit. The other unit may be composed of only one molecule, or two or more molecules may be used in combination. In the case of using two or more molecules in combination, the above-mentioned two or more molecules may be mixed and polymerized blocks and silicone units to form a copolymer, or each molecule may constitute a block and then constitute a copolymer with the silicone unit. In addition, in the case of using two or more molecules in combination as other units, hydroxyl groups may be introduced into all types of molecules, or hydroxyl groups may be introduced into only some types of molecules.
[0045] As a preferred example of silicone copolymer, a silicone copolymer composed of acrylate-modified silicone oil as a silicone unit and methyl methacrylate and 2-hydroxyethyl methacrylate as other units can be cited. As shown in the examples below, the surface layer 3 formed by using this silicone copolymer has a particularly excellent effect of improving the sliding property, and as a result, it shows a high effect of suppressing the sliding sound during durability.
[0046] In the silicone copolymer, the siloxane concentration is 95 mol% or more and less than 100 mol%, or 40 mol% or more and 70 mol% or less. The siloxane concentration is the ratio of the siloxane unit (Si-O unit) in all monomer units in the whole silicone copolymer expressed in mol%. In other words, it indicates the ratio of the number of siloxane units in the total number of siloxane units constituting the silicone unit and the number of monomer units constituting other units.
[0047] In the surface layer 3 of the conveyor belt 1, the silicone copolymer functions as a modifier for improving the sliding property. By making the siloxane concentration in the silicone copolymer 40 mol% or more, the sliding property improvement effect can be fully exerted. In addition, the wear resistance of the surface layer 3 is also improved. Since the sliding property of the surface layer 3 is improved, the scraper can slide smoothly on the surface of the conveyor belt 1, and the generation of sliding sound is suppressed. From the viewpoint of further improving the effect of improving the sliding property and the wear resistance, the siloxane concentration is particularly preferably 45 mol% or more, and more particularly preferably 50 mol% or more, 55 mol% or more, and 60 mol% or more.
[0048] On the other hand, even if the siloxane concentration is too high, the wear resistance of the surface layer 3 will become lower. This is because the hardness of the surface layer 3 becomes too low due to the poor curing of the resin composition. When the scraper and the conveyor belt 1 are brought into contact and slide, the surface layer 3 is easily worn by the scraper. The wear of the surface layer 3 damages the effect of improving the sliding property brought by the surface layer 3, which becomes the cause of the sliding sound. By suppressing the siloxane concentration to less than 70 mol%, the surface layer 3 can be fully cured to improve the wear resistance. As a result, even when durable, the sliding property can be maintained at a higher state, which can suppress the generation of sliding sound. The adhesion of the surface layer 3 to the base layer 2 also becomes higher. From the above viewpoint, the content ratio of the siloxane unit in the silicone copolymer can be more than 40 mol% and less than 70 mol%. This is because the curability of the resin composition forming the surface layer 3 is excellent, and as a result, the wear resistance and durable sliding property of the surface layer 3 are improved, and it is not easy to produce sliding sound.
[0049] On the other hand, if the siloxane concentration becomes higher, then different from the above view, the friction coefficient of the surface layer 3 becomes very low, and the force received from the cleaning blade becomes weaker. Thus, the wear resistance and durable sliding properties of the surface layer 3 are improved, and the sliding sound is suppressed. It is speculated that this is due to the effect brought about by the reduction of the friction coefficient exceeding the influence of the curability of the resin composition. From this viewpoint, the siloxane concentration in the silicone copolymer can be more than 95 mol%. More preferably, it is more than 96 mol%. On the other hand, if the siloxane concentration is 100 mol%, it does not have a reaction point with the fluororesin, so the silicone copolymer is not fixed, and the wear resistance and durable sliding properties are poor, and it becomes easy to produce sliding sound. Therefore, from the above viewpoint, the siloxane concentration in the silicone copolymer can be more than 95 mol% and less than 100 mol%. In addition, the siloxane concentration in the silicone copolymer is more preferably less than 99 mol%, and more preferably less than 98 mol%.
[0050] In the silicone copolymer, the siloxane concentration can be adjusted by, for example, selecting the ratio of silicone units to other units constituting the silicone copolymer. Furthermore, if other units are in the form of other units having hydroxyl groups and other units not having hydroxyl groups, such as methyl methacrylate and 2-hydroxyethyl methacrylate exemplified above, the concentration of hydroxyl groups can be adjusted in addition to the siloxane concentration in the silicone copolymer.
[0051] In the resin composition constituting the surface layer 3, the amount of silicone copolymer added is 1 phr or more and 5 phr or less, that is, 1 part by mass or more and 5 parts by mass or less relative to 100 parts by mass of the total of the fluororesin and the isocyanate cured product. By making the amount of silicone copolymer added 1 phr or more, the effect of improving the sliding property and wear resistance brought by the silicone copolymer and the effect of suppressing the sliding sound during durability brought about by the silicone copolymer can be fully exerted in the surface layer 3. The amount of silicone copolymer added is more preferably 2 phr or more.
[0052] On the other hand, by suppressing the addition amount of the silicone copolymer to 5 phr or less, and thus cooperating with the effect of suppressing the siloxane concentration in the silicone copolymer to 70 mol % or less, it is possible to avoid poor curing of the surface layer 3 and improve the wear resistance, and it is possible to effectively suppress the sliding sound during durability. The adhesion of the surface layer 3 to the base layer 2 is also improved. The addition amount of the silicone copolymer is more preferably 4 phr or less.
[0053] The resin composition constituting the surface layer 3 may also contain other components such as additives appropriately on the basis of the above-mentioned fluororesin, isocyanate curing agent, and silicone copolymer. As additives, various additives similar to those that can be added to the base layer 2, such as conductive agents, fillers, release agents, flame retardants, leveling agents, defoamers, and organic solvents may be listed.
[0054] As the leveling agent, a fluorine-based or silicone-based leveling agent is particularly preferred. If the surface layer 3 contains a fluorine-based or silicone-based leveling agent, the surface smoothness of the surface layer 3 is improved. As a result, the generation of sliding sound associated with the contact and sliding with the cleaning blade can be particularly effectively suppressed. When the siloxane concentration in the silicone copolymer becomes higher (for example, when it is 95 mol% or more), the surface smoothness of the surface layer 3 is easily reduced due to the influence of the curability of the composition. However, if the surface layer 3 contains a fluorine-based or silicone-based leveling agent, the reduction in the surface smoothness of the surface layer 3 is suppressed.
[0055] The amount of the leveling agent added to the resin composition constituting the surface layer 3 is preferably 0 phr to 5 phr, that is, preferably 0 to 5 parts by mass based on 100 parts by mass of the total of the fluororesin and the isocyanate cured product.
[0056] The microhardness of the surface of the surface layer 3 constituted as a cured body of the resin composition described above can be 30 N / mm 2 Above and 200N / mm 2 The microhardness of the surface can be measured using a microhardness tester. The load applied to the stylus during the measurement can be set to 5.0 mN, for example. The microhardness of the surface of the surface layer 3 is 30 N / mm 2 In the above case, the wear resistance of the surface layer 3 becomes high, and a high effect is shown in suppressing the sliding sound during durability. Furthermore, the micro hardness is more preferably 50N / mm 2 Above, 70N / mm 2 On the other hand, the micro hardness of the surface layer 3 is 200N / mm 2 In the following case, it is easy to ensure the bending resistance of the conveyor belt 1, and further, it is possible to effectively suppress the generation of sliding noise caused by surface deformation associated with bending. The micro hardness is more preferably 170 N / mm 2 Below, 150N / mm 2 the following.
[0057] The thickness of the surface layer 3 is not particularly limited. However, it is preferably suppressed to be thinner than the base layer 2. In addition, if the thickness of the surface layer 3 is set to 25 μm or more, it is easy to effectively exert the characteristics exhibited by the cured body of the resin composition containing the silicone copolymer, such as improved sliding properties and wear resistance. On the other hand, by suppressing the thickness of the surface layer 3 to 60 μm or less, it is easy to maintain the high bending resistance of the conveyor belt 1.
[0058] The conveyor belt 1 involved in the present embodiment can be manufactured in the following manner. First, a base layer 2 is formed. Regarding the base layer 2, a base layer forming material in the form of a coating material is appropriately applied using a solvent or the like to the outer peripheral surface of a cylindrical or columnar mold and dried. Heat treatment can also be performed as needed. As a coating method, dip coating, a dispenser coating method (nozzle coating method), a roller coating method, a ring coating method, etc. can be listed. Next, a resin composition for a surface layer is applied to the surface of the formed base layer 2 and cured, thereby forming a surface layer 3. At this time, heat treatment is performed as needed, thereby promoting the curing of the resin composition. The application of the resin composition can use various methods similar to the methods listed above for the formation of the base layer 2. Finally, the mold is removed, and a conveyor belt 1 having a surface layer 3 formed on the outer peripheral surface of the base layer 2 can be obtained. In this way, the surface layer 3 can be formed by applying a liquid composition, thereby simplifying the manufacturing process of the conveyor belt 1, and the cost required for manufacturing the conveyor belt 1 can be suppressed to a lower level.
[0059] Example
[0060] Hereinafter, the present invention will be described in detail using Examples and Comparative Examples. The present invention is not limited to the following Examples.
[0061] [Preparation of samples]
[0062] (1) Synthesis of silicone copolymers
[0063] First, a silicone copolymer used as a silicone modifier when forming the surface layer is synthesized.
[0064] The following raw materials were used for the synthesis of the silicone copolymer.
[0065] ·Methyl methacrylate (manufactured by Tokyo Chemical Industry) (molecular weight: 100.12)
[0066] ·Butyl methacrylate (manufactured by Tokyo Chemical Industry) (molecular weight: 128.17)
[0067] ·2-Hydroxyethyl methacrylate (manufactured by Tokyo Chemical Industry) (molecular weight: 130.14)
[0068] Acrylate-modified silicone oil ("X-22-174DX" manufactured by Shin-Etsu Industries) (molecular weight: 4600, number of siloxane units per molecular chain: 60.45)
[0069] · Free radical polymerization initiator: 1,1'-azobis(cyclohexane-1-carbonitrile) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (molecular weight: 244.34)
[0070] As silicones A to J, the raw materials shown in the following Table 1 were used respectively, and silicone copolymers were synthesized by the following method. First, three raw materials shown in Table 1 and methyl isobutyl ketone (MIBK) were added to a 0.5L reaction flask so that the solid content reached 50%. After nitrogen bubbling was performed for 5 minutes while stirring the contents of the flask, the temperature of the internal liquid was maintained at 100°C and a polymerization reaction was performed for 10 hours. Thereafter, MIBK was added so that the solid content reached 30%, and silicones A to J were prepared to obtain a copolymer solution.
[0071] Table 1 shows the amount of each raw material used in the synthesis of silicones A to J (unit: g). It also shows the siloxane concentration (unit: mol %) calculated based on the amount of each raw material used. In addition, Table 1 also records commercially available hydroxy-modified silicones and non-modified silicones and their siloxane concentrations. Commercially available hydroxy-modified silicones and non-modified silicones are shown below.
[0072] Silicone K (hydroxy-modified silicone): "Silaplane FMDA21" manufactured by JNC, siloxane concentration: 96 mol%, solid content: 100%
[0073] Silicone L (hydroxy-modified silicone): "Silaplane FMDA26" manufactured by JNC, siloxane concentration: 99 mol%, solid content: 100%
[0074] Silicone M (non-modified silicone oil): "KF-54" manufactured by Shin-Etsu Industries, siloxane concentration: 100 mol%, solid content: 100%
[0075] Table 1
[0076]
[0077] (2) Preparation of surface layer resin composition
[0078] Next, a resin composition for forming a surface layer is prepared using a silicone modifier composed of the silicone copolymer synthesized as described above.
[0079] When preparing the composition, the following materials were used as raw materials other than the silicone copolymer. The purpose of using two kinds of fluororesins here is that the two kinds of fluororesins impart different hardnesses when cured, and the microhardness of the surface of the resin composition can be changed by the mixing ratio of the two kinds of fluororesins. Both fluororesins have hydroxyl groups.
[0080] Fluororesin 1: Obbligato SS0054 main agent manufactured by AGC COAT-TECH (solid content 46%)
[0081] Fluororesin 2: Obbligato SS0062 main agent manufactured by AGC COAT-TECH (solid content 38%)
[0082] Isocyanate curing agent 1: "Obbligato SS0054 curing agent" manufactured by AGC COAT-TECH (solid content 83%)
[0083] Isocyanate curing agent 2: "Obbligato SS0062 Curing Agent" manufactured by AGC COAT-TECH (solid content 42%)
[0084] The components shown in the following Table 2 are mixed to prepare compositions A-1 to A-7, compositions B to J, compositions K-1 to K-4, and compositions L to M. At this time, the components shown in Table 2 are placed in a glass bottle and stirred and mixed by blades for 5 minutes. In addition, for compositions K-1 to K-4 and compositions L to M, instead of using the above-mentioned synthesized silicone copolymer as a silicone modifier, a commercially available silicone copolymer is used directly. In Table 2, in addition to the mass of each component (unit: g), the amount of silicone modifier added in the composition is also shown (unit: phr - the added mass calculated for the solid content relative to a total of 100 parts by mass of the fluororesin and the isocyanate cured product).
[0085] Table 2
[0086]
[0087] (3) Production of conveyor belt
[0088] As base materials, the following five kinds of polyimides were prepared.
[0089] PI-1: HCI-1300 manufactured by Hitachi Chemical (elastic modulus 5 GPa)
[0090] PI-2: Mixed HCI-1300 and HCI-1100 manufactured by Hitachi Chemical (mixing ratio 1:2) (elastic modulus 3 GPa)
[0091] PI-3: Mixed HCI-1300 and HCI-1200M manufactured by Hitachi Chemical (mixing ratio 1:1) (elastic modulus 7 GPa)
[0092] PI-4: HCI-1100 manufactured by Hitachi Chemical (elastic modulus 2 GPa)
[0093] PI-5: HCI-1200M manufactured by Hitachi Chemical (elastic modulus 9 GPa)
[0094] The above-mentioned base materials were applied to the surface of a cylindrical mold by dip coating, and heated at 120°C for 30 minutes, 150°C for 10 minutes, 200°C for 10 minutes, 250°C for 10 minutes, and 350°C for 10 minutes to form a base layer. At this time, the thickness of the base layer was controlled by the solid content of the coating and the pulling speed of the mold, as shown in Tables 3 and 4.
[0095] Next, a surface layer is formed on the surface of the base layer. The surface layer is formed by applying the above-formed resin compositions on the surface of the base layer by a dip coating method, and further heating at 160°C for 30 minutes to induce a curing reaction. The thickness of the surface layer is set to 45 μm in all samples. Finally, the mold is removed to produce the conveyor belts involved in Examples 1 to 19 and Comparative Examples 1 to 11. In addition, for Examples 18 and 19, a fluorine-based or silicone-based leveling agent (5 phr) is added to the resin composition.
[0096] Fluorine-based leveling agent: "Surflon S-658" manufactured by AGC Seimi Chemical
[0097] Silicone leveling agent: "x-22-4515" manufactured by Shin-Etsu Industries
[0098] [Evaluation method]
[0099] The following evaluations were performed on each of the conveyor belts produced above.
[0100] (1) Microhardness of the surface
[0101] Regarding the form of a conveyor belt having a surface layer formed on a base layer, the microhardness of the surface layer formed using each resin composition was measured. The measurement was performed using a microhardness meter. The load applied to the stylus during the measurement was set to 5.0 mN.
[0102] (2) Sliding sound
[0103] Each conveyor belt is set on the WF-C20590 paper conveying unit manufactured by Seiko Epson to rotate at a circumferential speed of 420 mm / second. The case where no sliding sound is generated for more than 300 hours is evaluated as "A+". In addition, the case where the sliding sound is generated in more than 270 hours and less than 300 hours is set as "A", the case where the sliding sound is generated in more than 240 hours and less than 270 hours is set as "B", and the case where the sliding sound is generated in less than 240 hours is set as "C". In the case where the evaluation results are A+, A, and B, it can be determined that the generation of sliding sound during durability is fully suppressed. On the other hand, in the case where the evaluation result is C, it is determined that the suppression of sliding sound during durability is insufficient.
[0104] (3) Wear resistance
[0105] Each conveyor belt was set on the above-mentioned paper conveying unit, and a durability test was carried out to rotate it for 240 hours at a circumferential speed of 420 mm / second. The film thickness before and after the durability test was measured by an eddy current meter, and the difference in film thickness (reduction) was set as the wear amount. The case where the wear amount was less than 3 μm was evaluated as "A", the case where the wear amount exceeded 3 μm and was less than 5 μm was evaluated as "B", and the case where the wear amount exceeded 5 μm was evaluated as "C". In the case where the evaluation results are A and B, it can be judged that the wear resistance is sufficient. On the other hand, in the case where the evaluation result is C, it is judged that the wear resistance is insufficient.
[0106] (4) Surface smoothness
[0107] Each conveyor belt was set on a cylindrical mold with a diameter of 8.2 cm, and the surface smoothness was evaluated. The average roughness (Rz) of ten points was measured by a roughness meter ("SURFCOM1400D" manufactured by ACCRETECH) in accordance with JIS B 0603:1994. The case where Rz is less than 0.8μm is evaluated as "A", the case where Rz is 0.8μm or more and less than 1μm is evaluated as "B", and the case where Rz is 1.0μm or more is evaluated as "C". When the evaluation results are A and B, it can be determined that the surface smoothness is sufficient. On the other hand, when the evaluation result is C, it is determined that the surface smoothness is insufficient.
[0108] (5) Bending resistance
[0109] Each conveyor belt was set on the above-mentioned paper conveying unit, and a durability test was carried out by rotating it at a peripheral speed of 420 mm / sec for 240 hours. After the durability test, the surface of the surface layer was visually observed, and the case where no cracks were observed on the surface layer was set as "A". In addition, the case where there was only one crack was evaluated as "B", and the case where there were two or more cracks was evaluated as "C". In the case where the evaluation results were A and B, it can be judged that the bending resistance is sufficient. On the other hand, in the case where the evaluation result was C, it was judged that the bending resistance was insufficient.
[0110] (6) Durable sliding properties
[0111] Each conveyor belt was set on the above-mentioned paper conveying unit, and a durability test was carried out in which it was rotated at a circumferential speed of 420 mm / sec for 240 hours. The friction coefficient before and after the durability test was measured by a friction coefficient measuring instrument (HEIDON Type94i manufactured by Shinto Science), and the change in the friction coefficient was recorded. Based on the value before durability, the case where the change (increase) of the friction coefficient is less than 5% is evaluated as "A+", the case where the change of the friction coefficient is 5% or more and less than 10% is evaluated as "A", the case where the change of the friction coefficient is 10% or more and less than 15% is evaluated as "B", and the case where the change of the friction coefficient is 15% or more is evaluated as "C". In the case where the evaluation results are A+, A, and B, it can be determined that the durable sliding property is sufficient. On the other hand, in the case where the evaluation result is C, it is determined that the durable sliding property is insufficient.
[0112] [Evaluation results]
[0113] The following Tables 3 and 4 show the configuration and evaluation results of the conveyor belts involved in Examples 1 to 19 and Comparative Examples 1 to 11. The upper section shows the type of composition used in forming the surface layer (the above-mentioned compositions A-1 to A7, compositions B to J, compositions K1 to K4, and compositions L to M), the siloxane concentration and addition amount of the silicone modifier, the measured value of the microhardness, and the type, elastic modulus, and thickness of the resin used in forming the base layer. The lower section shows the evaluation results of the conveyor belts.
[0114]
[0115] Table 4
[0116]
[0117] According to Table 3, in the conveyor belts of Examples 1 to 14, the base layer is composed of a polyimide having an elastic modulus of 3 GPa or more and 7 GPa or less, and the surface layer is composed of a cured product of a resin composition to which a fluororesin having a hydroxyl group and a silicone modifier in an amount of 1 phr or more and 5 phr or less are added. The silicone modifier has a hydroxyl group, and the content of the siloxane unit is 40 mol% or more and 70 mol% or less. Corresponding to the situation where the conveyor belt has such a structure, in any of Examples 1 to 14, the evaluation results of the sliding sound are all above the evaluation B, and the effect of suppressing the sliding sound during durability is fully obtained. Furthermore, in the above-mentioned embodiments, the wear resistance, bending resistance, and durable sliding resistance of the surface layer are also evaluated as B or more, and the excellence of the above-mentioned characteristics can be explained as the effect of suppressing the sliding sound. In the above-mentioned embodiments, the surface smoothness of the surface layer is also increased.
[0118] On the other hand, according to Table 4, in Comparative Examples 1 to 8 and 11, the structure of the conveyor belt does not satisfy any of the above-listed requirements. In the above Comparative Examples 1 to 8 and 11, the evaluation results of the sliding sound are all C, and the sliding sound during the durability cannot be fully suppressed. Regarding other evaluation results, at least the durable sliding property is also as low as the evaluation C. The following is a study of each comparative example.
[0119] In Comparative Example 11, as the silicone modifier added to the surface layer, a copolymer containing silicone units and other units was not used, but silicone oil itself was used instead. Therefore, sufficient durable sliding properties were not obtained in the surface layer. As a result, the sliding suppression effect during durability was not fully achieved.
[0120] In Comparative Examples 1 to 4, resin compositions containing silicone copolymers as silicone modifiers were used, but the siloxane concentration in the silicone copolymers or the amount of silicone copolymer added was not within the above-described predetermined range. In Comparative Example 1, the siloxane concentration in the silicone modifier was less than 40 mol%. Accordingly, sufficient durable sliding properties were not obtained in the surface layer. On the other hand, in Comparative Example 2, the siloxane concentration was greater than 70 mol%. Accordingly, sufficient durable sliding properties were not obtained in the surface layer. Based on the above results, it can be said that it is crucial to set the siloxane concentration to a range of 40 mol% or more and 70% or less in order to ensure high durable sliding properties in the surface layer and to sufficiently contribute to suppressing sliding sounds during durability.
[0121] In Comparative Example 3, the amount of silicone modifier added to the surface layer forming composition is less than 1 phr. Accordingly, sufficient durable sliding properties are not obtained in the surface layer. On the other hand, in Comparative Example 4, the amount of silicone modifier added is more than 5 phr. Accordingly, sufficient durable sliding properties are not obtained in the surface layer. Based on the above results, it can be said that it is crucial to set the amount of silicone modifier added to the surface layer forming composition to a range of 1 phr or more and 5 phr or less in order to ensure durable sliding properties in the surface layer and to sufficiently contribute to suppressing sliding sounds during durability.
[0122] In Comparative Example 5, the elastic modulus of the base layer is lower than 3 GPa. Corresponding to this situation, the durable sliding property becomes low. On the other hand, in Comparative Example 6, the elastic modulus of the base layer is higher than 7 GPa. Corresponding to this situation, the bending resistance and the durable sliding property become low. According to the above results, it can be said that it is very important to make the base layer consist of a polyimide having an elastic modulus of more than 3 GPa and less than 7 GPa in order to ensure high durable sliding property and high bending resistance as a conveyor belt as a whole and to fully suppress the sliding sound during durability. When the constituent material of the base layer is set to polyamide-imide, the same effect can also be obtained.
[0123] In Comparative Examples 7 and 8, since the silicone modifier does not have a hydroxyl group, the silicone modifier is not fixed to the fluororesin. Correspondingly, the wear resistance in the surface layer is slightly poor, and sufficient durable sliding properties are not obtained. According to the above results, in order to ensure high durable sliding properties and high wear resistance for the entire conveyor belt and to sufficiently suppress sliding noise during durability, it is necessary to make the silicone modifier have a hydroxyl group.
[0124] In addition, Examples 1 to 14 were compared with each other. When Examples 1 to 4 were compared with each other, in which only the siloxane concentration in the silicone modifier was different, in Examples 1, 2, and 4 in which the siloxane concentration was 45 mol% or more, particularly excellent sliding sound suppression effect and durable sliding property were obtained compared with Example 3 in which the siloxane concentration was less than 45 mol%. In particular, in Example 1 in which the siloxane concentration was 60 mol% or more, the sliding sound suppression effect and durable sliding property became very high. According to the above results, it can be said that by increasing the siloxane concentration in the silicone modifier to 45 mol% or more, and further increasing it to 60 mol% or more, the durable sliding property of the surface layer can be effectively improved, and as a result, the sliding sound suppression effect becomes high. However, when Example 5 in which the siloxane concentration was further increased to 70 mol% was compared with Example 1, the sliding sound suppression effect was slightly lower. According to the above results, the siloxane concentration in the silicone modifier is particularly preferably 45 mol% or more, and further particularly preferably 60 mol% or more, and it can be said that it is preferably suppressed to less than 70 mol% with a margin.
[0125] When comparing Examples 1, 6, and 7, which differ only in the amount of silicone modifier added, particularly high durable sliding properties and sliding noise suppression effects were obtained in Example 1, in which the amount of silicone modifier added was 2 phr or more and 3 phr or less. In addition, when comparing Examples 1, 11, and 12, which differ only in the microhardness of the surface layer, the sliding noise suppression effect and bending resistance of the one with higher microhardness were slightly reduced, while the sliding noise suppression effect, wear resistance, and durable sliding properties of the one with lower microhardness were slightly reduced. In Example 1, which has an intermediate microhardness, wear resistance, durable sliding properties, and bending resistance were well-balanced, and it can be said that particularly high sliding noise suppression effects were obtained.
[0126] In each example except Example 10, the silicone modifier is composed of a silicone copolymer formed by acrylate-modified silicone oil, methyl methacrylate and 2-hydroxyethyl methacrylate, but in Example 10, butyl methacrylate (Silicone F in Table 1) is used instead of methyl methacrylate. Example 10 is different from Example 1 only in the molecular structure of the silicone modifier, but Example 1 has an excellent sliding sound suppression effect. Based on this, it can be said that by using a silicone copolymer formed by acrylate-modified silicone oil, methyl methacrylate and 2-hydroxyethyl methacrylate as a silicone modifier, sliding sound can be effectively suppressed. It is speculated that when other units with a small number of carbon atoms are used as other units constituting the silicone copolymer together with the silicone unit, the sliding property improvement effect brought about by the silicone unit is significantly exhibited.
[0127] Examples 1, 8, and 9 differ from each other in the elastic modulus of the base layer. In Example 1, in which the elastic modulus is 4 GPa or more and 6 GPa or less, the durable sliding property is higher than that of any of Examples 8 and 9. The bending resistance is also higher. Accordingly, if the elastic modulus of the base layer is 4 GPa or more and 6 GPa or less, both the durable sliding property and the bending resistance are excellent, and as a result, it can be said that a higher sliding sound suppression effect is obtained. In addition, Examples 1, 13, and 14 differ from each other in the thickness of the base layer. In Example 1, compared with Example 14 in which the base layer is thicker, the bending resistance is excellent, and as a result, a higher sliding sound suppression effect is obtained. In comparison with Example 13 in which the base layer is thinner, the sliding sound suppression effect is also higher. In addition, in Example 13, since the base layer becomes thinner, slight wrinkles are generated in the conveyor belt when the conveyor belt is assembled to the paper conveying unit, and the sliding sound suppression effect is not as high as that in Example 1.
[0128] In addition, according to Table 3, the conveyor belts of Examples 15 to 19 are all cured products of a resin composition in which the base layer is composed of a polyimide having an elastic modulus of 3 GPa or more and 7 GPa or less, and the surface layer is composed of a fluororesin having a hydroxyl group and a silicone modifier in an amount of 1 phr or more and 5 phr or less. The silicone modifier has a hydroxyl group, and the content ratio of the siloxane unit is 95 mol% or more and less than 100 mol%. Corresponding to the situation where the conveyor belt has such a structure, in any of Examples 15 to 19, the evaluation results of the sliding sound are all evaluated as A or more, and the effect of suppressing the sliding sound during durability is very high. Furthermore, in the above-mentioned examples, the wear resistance, bending resistance, and durable sliding resistance of the surface layer are evaluated as A or more, and the excellent properties of the above-mentioned characteristics can be interpreted as the effective effect of suppressing the sliding sound.
[0129] On the other hand, according to Table 4, in Comparative Examples 2, 9 to 11, the structure of the conveyor belt does not satisfy any of the above-listed requirements. In the above Comparative Examples 2, 9 to 11, the evaluation results of the sliding sound are all C, and the sliding sound during the durability cannot be fully suppressed. Regarding other evaluation results, at least the durable sliding property is as low as evaluation C. The following is a study of each comparative example.
[0130] In Comparative Examples 2, 9 to 11, resin compositions containing silicone polymers as silicone modifiers were used, but the siloxane concentration in the silicone copolymer or the amount of silicone copolymer added was not within the above-mentioned predetermined range. In Comparative Example 2, the siloxane concentration in the silicone modifier was less than 95 mol%. Accordingly, sufficient durable sliding properties were not obtained in the surface layer. On the other hand, in Comparative Example 11, the siloxane concentration was 100 mol%. Accordingly, sufficient durable sliding properties were not obtained in the surface layer. Based on the above results, it can be said that it is crucial to make the siloxane concentration in the range of 95 mol% or more and less than 100% in order to ensure high durable sliding properties in the surface layer and to sufficiently contribute to suppressing sliding sounds during durability.
[0131] In Comparative Example 9, the amount of silicone modifier added to the surface layer forming composition is less than 1 phr. Accordingly, sufficient durable sliding properties are not obtained in the surface layer. On the other hand, in Comparative Example 10, the amount of silicone modifier added is more than 5 phr. Accordingly, sufficient durable sliding properties are not obtained in the surface layer. Based on the above results, it can be said that it is crucial to set the amount of silicone modifier added to the surface layer forming composition to a range of 1 phr or more and 5 phr or less in order to ensure durable sliding properties in the surface layer and to sufficiently contribute to suppressing sliding sounds during durability.
[0132] Furthermore, when Examples 15 to 19 are compared with each other, it is found that when the siloxane concentration in the silicone copolymer is further increased, the surface smoothness tends to decrease (Examples 15 and 17), and the decrease in surface smoothness can be suppressed by adding a fluorine-based or silicone-based leveling agent.
[0133] As mentioned above, although embodiment of this invention is described in detail, this invention is not limited to the said embodiment, Various changes can be made within the range which does not deviate from the summary of this invention.
[0134] Description of Reference Numerals
[0135] 1: conveyor belt;
[0136] 2: Grassroots;
[0137] 3: Surface layer;
[0138] A: Fluororesin;
[0139] B: isocyanate curing agent;
[0140] C: Silicone copolymer.
Claims
1. A conveyor belt for an image forming device, wherein: The conveyor belt for the image forming device comprises a cylindrical base layer and a surface layer formed on the outer peripheral surface of the base layer. The base layer contains at least one of polyimide and polyamide-imide, The base layer has an elastic modulus of 3 GPa or more and 7 GPa or less, The surface layer is formed as a cured product of a resin composition comprising a fluororesin having a hydroxyl group, an isocyanate curing agent, and a silicone copolymer. The silicone copolymer is a copolymer including a silicone unit having a siloxane skeleton and other units not having a siloxane skeleton, and the silicone copolymer has a hydroxyl group. The content ratio of the siloxane unit in the silicone copolymer is 95 mol% or more and less than 100 mol%, The amount of the silicone copolymer added in the resin composition is 1 part by mass or more and 5 parts by mass or less relative to 100 parts by mass in total of the fluororesin and the isocyanate curing agent.
2. A conveyor belt for an image forming device, wherein: The conveyor belt for the image forming device comprises a cylindrical base layer and a surface layer formed on the outer peripheral surface of the base layer. The base layer contains at least one of polyimide and polyamide-imide, The base layer has an elastic modulus of 3 GPa or more and 7 GPa or less, The surface layer is formed as a cured product of a resin composition comprising a fluororesin having a hydroxyl group, an isocyanate curing agent, and a silicone copolymer. The silicone copolymer is a copolymer including a silicone unit having a siloxane skeleton and other units not having a siloxane skeleton, and the silicone copolymer has a hydroxyl group. The content ratio of the siloxane unit in the silicone copolymer is 40 mol% or more and 70 mol% or less, The amount of the silicone copolymer added in the resin composition is 1 part by mass or more and 5 parts by mass or less relative to 100 parts by mass in total of the fluororesin and the isocyanate curing agent.
3. The conveyor belt according to claim 1 or 2, wherein: The surface layer contains a fluorine-based or silicone-based leveling agent.
4. The conveyor belt according to claim 1 or 2, wherein: The micro hardness of the surface layer is 30N / mm 2 Above and 200N / mm 2 the following.
5. The conveyor belt according to claim 1 or 2, wherein: The thickness of the base layer is 50 μm or more and 90 μm or less.
6. The conveyor belt according to claim 1 or 2, wherein: The silicone copolymer is composed of any one of methyl methacrylate, 2-hydroxyethyl methacrylate and trimethylolpropane as the other units, and acrylate-modified silicone oil and OH-modified silicone oil as the silicone units.
Citation Information
Patent Citations
Medium carrying belt
JP2001310836A
Transfer belt for ink jet and ink jet recording apparatus
JP2008094605A
Inkjet conveyance belt
JP2011073804A
Member for electrophotography
CN104718501A
Medium conveying belt
JP2002302287A